DIGITAL LITERACY SOCIALIZATION FOR STUDENTS ELEMENTARY SCHOOL STUDENTS IN THE RENZO EDUPARK CIBADAK SUKABUMI AREA - Amelia, Decenni; Maulidah, Neni; Ningrum, Desy Tya Maya; Andini, Tiara Suci; Septionia, Paquita (Yayasan Education and Social Center, 2023)
Digital literacy is defined as a person's ability to use computer devices to access various information in the digital space. Digital literacy is the ability to use information and communication technology. In addition, digital literacy is also defined as the ability to understand and use information in various formats and from various sources that are available everywhere. Social media is one form of digital technology development. Using social media has now become a daily lifestyle for the community, social media is not only used as entertainment but also used as a support for people's lives, exchanging messages, socializing with friends or relatives, studying, working, channeling talents, and can also be a forum for social activities carried out without the need to meet face to face. Based on the observations and results of the KKN FIP Ubhara Jaya Students carried out in the Renzo Edupark Cibadak Sukabumi area from October 24 to November 24, 2022, it was found that in the Renzo Edupark environmental area many elementary school students use social media as a means of entertainment and seeking information, but there are several problems that become the main focus so that the main background of this community service is carried out, namely; (1) they are not yet able to sort and choose which info is true and which is not, (2) they also have no restrictions in using social media, they can freely access pornographic content, violent content, and other non-educational content, so it is feared that this will become a threat to them in the future. For this reason, in this community service, there are 2 things that become the main focus to be socialized to elementary school students in the Renzo Edupark Cibadak Sukabumi area, (1) Socialization of digital literacy related to the importance of digital literacy in 21st century life so that students are not left behind by technological developments, and (2) Socialization of how to use good and correct social media to get various information and filter the content accessed by elementary school students. The output target of this abdimas is the publication of articles published in accredited national journals